Simulation-based parameter optimization and experimental assessment of single- and multi-dimple textures in full-film lubrication - Scharf, Raphael; Pusterhofer, Michael; Grün, Florian; Staudinger, Paul (Frontiers in Mechanical Engineering, 2026)
The specific geometrical modification of surfaces is a current field of research to enhance the tribological properties in lubricated sliding contacts. As many parameters influence the performance of textures, a numerical approach is used to identify optimal parameters for a single-dimple and multi-dimple textured convergent oil film gap. To ensure that such surface textures can be easily manufactured, the widely used milling manufacturing technique is employed. Additionally, a novel test methodology was implemented on a rheometer/tribometer to evaluate the performance of these textures in full-film lubrication. Both a numerical and an experimental approach are used. In this experimental methodology, the rotational speed, temperature, and minimum oil film gap are varied. The experiments show that the single-dimple texture leads to the highest load-carrying capacity. The drag force of both textures is similar at 23 °C and is lower than that of the untextured oil film gap. As the temperature increases, this beneficial effect of reducing drag is no longer observed. However, the load-carrying capacity of both textures remains higher than that of the untextured oil film gap.